2018
DOI: 10.1002/bjs.10771
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of delayed gastric emptying after pylorus-preserving versus pylorus-resecting pancreatoduodenectomy

Abstract: Pylorus-resecting pancreatoduodenectomy is not superior to pylorus-preserving pancreatoduodenectomy for reducing DGE or other relevant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 36 publications
6
40
1
3
Order By: Relevance
“…The German cohort was less likely to develop DGE than the Dutch cohort (10⋅9 versus 18⋅0 per cent). The main reason for DGE is postoperative complications 47,48 . As overall major complication rates were similar between cohorts in the present study and published DGE rates mostly vary between 15 and 40 per cent 49 , reporting or classification bias seems the most likely explanation for the difference in DGE rates.…”
Section: Discussionmentioning
confidence: 99%
“…The German cohort was less likely to develop DGE than the Dutch cohort (10⋅9 versus 18⋅0 per cent). The main reason for DGE is postoperative complications 47,48 . As overall major complication rates were similar between cohorts in the present study and published DGE rates mostly vary between 15 and 40 per cent 49 , reporting or classification bias seems the most likely explanation for the difference in DGE rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled trial [35] comparing PD with pylorus-resecting or pyloruspreserving did not showed significant difference in DGE rate. Finally, a recent metaanalysis [36] showed superiority for pylorus-resecting pancreaticoduodenectomy regarding DGE when all studies are included.…”
Section: Discussionmentioning
confidence: 99%
“…This currently largest RCT was designed and planned with the attempt to overcome the limitations of previous trials with non-blinded trial designs and missing adherence to consensus definitions for outcome parameters. We currently performed a systematic review and meta-analysis to give an update of critically appraised and quantitative data on the effectiveness and safety of pylorus-preserving compared to pylorus-resecting PD (58). Table 2 summarizes the available randomized trials.…”
Section: Resection Of the Pylorus Does Not Reduce Dgementioning
confidence: 99%
“…Table 2 summarizes the available randomized trials. Meta-analysis of the three existing RCTs showed no significant statistical difference between the two procedures for DGE and other relevant outcome parameters including postoperative pancreatic fistula, postpancreatectomy hemorrhage, intra-abdominal fluid collection/abscess, bile leakage, wound infection, pulmonary complications, mortality, reoperations, perioperative blood loss, duration of operation, and length of hospital stay (58). To account for differences in reconstruction techniques, sensitivity analyses were performed.…”
Section: Resection Of the Pylorus Does Not Reduce Dgementioning
confidence: 99%